METODE PEWARNAAN GRAF DALAM PENJADWALAN TENAGA KESEHATAN - Ade Novita Andriani (Journal of Hospital Administration and Management, 2021)
Scheduling is an important thing and must be owned by the hospital. Hospitals that still use the manual method to arrange the schedule of health workers still have many difficulties and shortcomings in doing so. For this reason, methods are needed so that the scheduling of health workers can be done easily and quickly. The method used is Observation and Documentation. The results obtained are based on the three journals discussed, namely that there are better results in preparing the schedule than using the previous method.